The Accounting Figuration of Business Statistics as a Foundation for the Spread of Economic Ideas - Suzuki, T (Pergamon, 2003)
The new accounting research has been devoted to illuminating the social and constitutive aspects of accounting. This has been done, however, in many cases, in the setting of micro managerial accounting. The effects of financial and macroeconomic accounting on modern economic society have not been examined in depth from an epistemological and critical viewpoint. This article attempts to develop a hypothesis that financial accounting (particularly, that of macro economic entities) has been centrally implicated in the process through which economic ideas and economic management have become ubiquitous in modern society. Accounting's power and the reason for its steady growth are sought in its various formalities rather than its representational capacity. Several factors that are considered to constitute the formalities form a self-perpetuating apparatus that facilitates the prevalence of accounting in modern economic society.